Leadership competencies and managerial competencies of nurse managers in Kuala Lumpur Hospital, Malaysia - Chin, Mary; Balang, Rekaya Vincent; Wider, Walton; Tanucan, Jem Cloyd M.; Sim, Hui Yen; Janjuy, Chamaipron (Jurnal Ners, 2024)
Introduction: The roles of nurse managers are crucial to the success of healthcare organizations, requiring specific skills and competencies. Accordingly, nurse managers are expected to possess leadership and management skills. Therefore, it is essential to investigate the relationship between leadership and managerial competencies among hospital nurse managers. This study seeks to determine the impact of three different leadership competencies, namely administrative skill, interpersonal skill, and conceptual skill, on the managerial competencies of nurse managers at Kuala Lumpur Hospital. Methods: This cross-sectional quantitative study adopted Northouse’s (2019) leadership competencies questionnaires and Mind Tool’s (2018) management skills assessment tool. A total of 247 participants, all of whom were nurse managers at the Kuala Lumpur Hospital, Malaysia, were recruited for this study. Multiple regression analysis was used to test the hypothesis. Results: The findings revealed that nurse managers at Kuala Lumpur Hospital possessed high levels of all three leadership skills and managerial competencies. However, the only significant predictor of managerial competencies among the respondents is the conceptual skill of leadership (beta = 0.820, p < 0.01). Conclusions: This study emphasizes conceptual skills (cognitive abilities, analytical reasoning, and decision-making) in predicting managerial competencies among nurse managers. Developing these skills is critical for effective leadership and smooth healthcare organization operations. Keywords: administrative skill, conceptual skill, interpersonal skill, leadership competencies, mental health